PREVALENCE OF SUBCLINICAL GASTROINTESTINAL PARASITIC INFECTION IN DAIRY ANIMALS - Saravanan, S; Dinakaran, A Manicavasaka; Muralidharan , J; Geetha , M; Selvaraju, G (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The spectrum of helminthic parasites was assessed by coprological survey made in cattle and buffaloes managed by local farmers. Predominant helminths were found to be nematodes with direct life cycle whereas cestodes and flukes were poorly represented. Prevalence was more in cross bred cattle than buffaloes and more positivity with increase in age was observed.